Self-Reported Nutrition Education Received by Australian Midwives before and after Registration - Jamila Arrish; Heather Yeatman; Moira Williamson (Journal of Pregnancy)
Educating midwives to provide nutrition advice is essential. Limited research focuses on midwives’ nutrition education. This paper explores self-reported nutrition education received by Australian midwives before and after registration. It draws on quantitative and qualitative data from a larger online survey conducted with the members of the Australian College of Midwives (response rate = 6.9%, n=329). Descriptive and content analyses were used. Of the midwives, 79.3% (n=261) reported receiving some nutrition education during, before, and/or after registration. However, some described this coverage as limited. It lacked sufficient focus on topics such as weight management, nutrition assessment, and nutrition for vulnerable groups. Continuing education often occurred through personal initiatives, such as the midwife enrolling in external courses or exploring issues on the Internet and with colleagues. The majority of participants indicated a need for increased nutrition education (94.2%, n=310) and guidelines tailored for them to provide nutrition advice (87.8%, n=289). Australian midwives may not be receiving adequate nutrition education to provide nutrition advice. Inclusion of evidence-based nutrition components in midwifery education and regular updates for practising midwives focusing on challenging nutrition issues is required to ensure that they are supported in this important role.